Photodynamic Therapy for the Treatment of Glioblastoma - Cramer, Samuel W.; Chen, Clark C. (Frontiers in Surgery, 2020)
Glioblastoma is the most common form of adult brain cancer and remains one of the deadliest of human cancers. The current standard-of-care involves maximal tumor resection followed by treatment with concurrent radiation therapy and the chemotherapy temozolomide. Recurrence after this therapy is nearly universal within two years of diagnosis. Notably, >80% of recurrence is found in the region adjacent to the resection cavity. The need for improved local control in this region, thus remains unmet. The FDA approval of 5-aminolevulinic acid (5-ALA) for fluorescence guided glioblastoma resection renewed interests in leveraging this agent as a means to administer photodynamic therapy (PDT). Here we review the general principles of PDT as well as the available literature on PDT as a glioblastoma therapeutic platform.